The effect of service quality on customer loyalty at PT. Pos Indonesia (persero), Unaaha branch Konawe regency - Melati Melati; Heriswanto Heriswanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to determine and explain the effect of service quality on customer loyalty at PT. Pos Indonesia (Persero), Konawe Regency Unaaha Branch. The approach used in this research is a quantitative approach. The population in this study were customers at PT. Pos Indonesia (Persero) Cabang Unaaha Konawe Regency. Service quality variable as an independent variable (X) on customer satisfaction (Y) at PT. This research uses simple linear regression analysis and the sample is 51 people. The schedule for the study was three months.The results of this study can be concluded that changes in service quality are positive and significant in increasing customer loyalty. This means that the better the quality of service provided to customers then higher of the level of customer loyalty to buy the same product in the future at PT. Pos Indonesia (Persero), Unaaha Branch. Besides, the changes in improving service quality are positive and significant in enhancing the customer loyalty. Therefore, the key to success that will be achieved in the future in enhancing the customer loyalty is by improving service quality.